A Novel Metastable Pentavalent Plutonium Solid Phase on the Pathway from Aqueous Plutonium(VI) to PuO2 Nanoparticles. Issue 49 (6th November 2019) - Kvashnina, Kristina O.; Romanchuk, Anna Yu.; Pidchenko, Ivan; Amidani, Lucia; Gerber, Evgeny; Trigub, Alexander; Rossberg, Andre; Weiss, Stephan; Popa, Karin; Walter, Olaf; Caciuffo, Roberto; Scheinost, Andreas C.; et al.
Abstract: Here we provide evidence that the formation of PuO2 nanoparticles from oxidized Pu VI under alkaline conditions proceeds through the formation of an intermediate Pu V solid phase, similar to NH4 PuO2 CO3, which is stable over a period of several months. For the first time, state‐of‐the‐art experiments at Pu M4 and at L3 absorption edges combined with theoretical calculations unambiguously allow to determine the oxidation state and the local structure of this intermediate phase. Abstract : Solid proof : The formation of a novel pentavalent plutonium solid phase was observed on the pathway from aqueous Pu VI to PuO2 nanoparticles by applying a high energy resolution fluorescence detection method at the Pu M4 and L3 edges and electronic structure calculations.